2019
DOI: 10.1103/physrevlett.122.124502
|View full text |Cite
|
Sign up to set email alerts
|

Is the Zero Reynolds Number Approximation Valid for Ciliary Flows?

Abstract: Stokes equations are commonly used to model the hydrodynamic flow around cilia on the micron scale. The validity of the zero Reynolds number approximation is investigated experimentally with a flow velocimetry approach based on optical tweezers, which allows the measurement of periodic flows with high spatial and temporal resolution. We find that beating cilia generate a flow, which fundamentally differs from the stokeslet field predicted by Stokes equations. In particular, the flow velocity spatially decays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…The presence of several harmonics in the x(t) and y(t) signals leads to reconstructions of the input velocities u x (t) and u y (t) , which significantly differ from x(t) and y(t) in amplitude, shape and phase. To verify the accuracy of the velocimetry method, we compare the OTV measurements with the numerical boundary element method (BEM) simulations (Wei et al 2019). We model the cell body and the pipette as a single axisymmetric object.…”
Section: Case Study: Unsteady Flow Around C Reinhardtiimentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of several harmonics in the x(t) and y(t) signals leads to reconstructions of the input velocities u x (t) and u y (t) , which significantly differ from x(t) and y(t) in amplitude, shape and phase. To verify the accuracy of the velocimetry method, we compare the OTV measurements with the numerical boundary element method (BEM) simulations (Wei et al 2019). We model the cell body and the pipette as a single axisymmetric object.…”
Section: Case Study: Unsteady Flow Around C Reinhardtiimentioning
confidence: 99%
“…Furthermore, we use slender body theory to represent the flagella. The shapes and deformations of the flagella are directly extracted from the experiment recordings and used in BEM simulations to compute the flow fields (see Wei et al (2019) for more details). In Fig.…”
Section: Case Study: Unsteady Flow Around C Reinhardtiimentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous studies of sensing assumed either oscillatory inviscid flow or steady viscous flow in the far field 14,20,33 and neglected the combined effects of viscosity and inertia in the near field. More recent studies have shown that, even in fluids dominated by viscosity at the microscopic scale, oscillating structures such as cilia have minute inertia yet they can still have profound long-lasting effects, resulting in flows governed importantly by both viscosity and inertia 34,35 . It is precisely the combination of these two effects that can effectively facilitate the detection of inert particles at the edge of a boundary layer, e.g.…”
mentioning
confidence: 99%